Cablegram from Max Bredig to Marianne Homburger, April 28, 1941 - Bredig, Max Albert (1941)
Max Bredig (1902-1977) tells his sister, Marianne Homburger (1903-1986) that he placed an order through the Chase National Bank.
Keywords: Homburger, Marianne, 1903-1986; Jewish Holocaust (1939-1945); Western Union Telegraph Company; Chase National Bank of the City of New York